Exploring the Landscape of Teaching and Learning English as a Second Language in India - Winson, V.R.V.; Arunkumar, Vardhanapu; Rao, Dadala Prakasha (CV. Bimbingan Belajar Assyfa, 2023)
This systematic review examines the challenges, opportunities, and ways forward for teaching and learning English as a second language in India. The study explores the current landscape of English language teaching in India, considering factors such as policy, curriculum, teaching methodologies, and technology integration. The review identifies the significant challenges learners and teachers face, including linguistic and cultural barriers, inadequate infrastructure, and limited teacher training. The study also highlights the opportunities and potential solutions to overcome these challenges, such as utilizing innovative teaching strategies and digital technologies. Based on the findings, the study suggests a way forward for developing English language teaching in India, emphasizing the need for comprehensive language policies, teacher development programs, and a learner-centered approach